Unwind: a musical biofeedback for relaxation assistance. Issue 8 (3rd August 2018) - Yu, Bin; Funk, Mathias; Hu, Jun; Feijs, Loe
ABSTRACT: Unwind is a musical biofeedback interface which combines nature sounds and sedative music into a form of New-Age music for relaxation exercises. The nature sounds respond to the user's physiological data, functioning as an informative layer for biofeedback display. The sedative music aims to induce calmness and evoke positive emotions. UnWind incorporates the benefits of biofeedback and sedative music to facilitate deep breathing, moderate arousal, and promote mental relaxation. We evaluated Unwind in a 2 × 2 factorial experiment with music and biofeedback as independent factors. Forty young adults performed the relaxation exercise under one of the following conditions after experiencing a stressful task: Nature sounds only (NS), Nature sounds with music (NM), and Auditory biofeedback with nature sounds (NSBFB), and UnWind musical biofeedback (NMBFB). The results revealed a significant interaction effect between music and biofeedback on the improvement of heart rate variability. The combination of music and nature sounds also showed benefits in lowering arousal and reducing self-report anxiety. We conclude with a discussion of UnWind for biofeedback and the wider potential of blending nature sounds with music as a musical interface.